Plant–Vitamin–Microorganism Interaction in Hydroponic Melon Cultivation - Vanessa Ribeiro; Eduardo Pradi Vendruscolo; Jessé Santarém Conceição; Sebastião Ferreira de Lima; Flávio Ferreira da Silva Binotti; Fernanda Pacheco de Almeida Prado Bortolheiro; Carlos Eduardo da Silva Oliveira; Edilson Costa; Luc Lafleur (Horticulturae)
The study of the application of biostimulants in agriculture aims to increase production and improve the efficient use of physical space and agricultural inputs, thus contributing to the sustainability of production systems. One of the new challenges is to verify the effects of joint application of these products to identify possible interactions during crop development. In this context, the present study aimed to evaluate the biostimulant potential of the isolated and combined use of nicotinamide and Azospirillum brasilense in developing cantaloupe melon plants and fruits. The treatments consisted of foliar application (combined and isolated) of nicotinamide (300 mg L−1) and A. brasilense (2 mL L−1). The results revealed that applying biostimulants positively influences gas exchange and vegetative growth of plants, especially in the root system. However, although the isolated application of each biostimulant resulted in greater effectiveness in terms of transpiration, stomatal conductance, and net CO2 assimilation, which provided an increase in the soluble solids content, the combined application of the two biostimulants resulted in significant gains in the growth of vegetative organs and fruits. Furthermore, combined applications of nicotinamide plus A. brasilense favored the development of biometric characteristics and fruit fresh weight, while isolated applications increased soluble solids content.